মুক্তির সংগ্রাম - আনিসুজ্জামান; বণিক, সুবলকুমার; হোসেন, মোবারক; দেব, দেবাশীষ; সোম, বীরেন 1948-
Articles on the history of freedom movements in undivided Bengal, India and Bangladesh, from 1757 to 1971.